CULTURAL INFLUENCE AND SOCIAL SUPPORT TOWARDS THE DEPRESSION, ANXIETY, AND STRESS LEVELS (CASE STUDY) - Azwin, Khalifatul; Muin, Muhamad Fathul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The students mental health has been a global issue. Students from various regions in Indonesia are more likely to be affected by mental health disorders caused by encountering an unfamiliar environment. Therefore, this study aims to determine the effect of culture shock and social support on depression, anxiety, and stress that is experienced. This research is a cross-sectional study using primary data taken from Polytechnic of Statistics students in the academic year of 2018/2019. The questionnaire refers to DASS-21, MOS Social Support, and 12 cultural concussion items formed by Taft and Mumford. The data obtained were analyzed by the PLS-SEM method. The results found that the prevalence of depression, anxiety, and stress experienced by students are 25.36%, 58.41%, and 17.20%, respectively. In addition, the high occurence of culture shock makes the depression, anxiety and stress experienced increased. Conversely, there was no significant effect between social support and culture shock, depression, anxiety, and stress. The high prevalence of depression, anxiety, and stress experienced by students have a negative impact. All related parties are expected to help overcome students' mental health disorders.